ABOUT VALUE OF EXTERNAL FORM OF PRESENTATION OF EDUCATIONAL INFORMATION BY FACILITIES MULTIMEDIA IN INNOVATIVE EDUCATIONAL RESOURCES - Denisenko С.М. (Journal of Information Technologies in Education (ITE), 2011)
In the article the question of presentation of educational material by multimedia in electronic educational resources is considered. The value of external form of representation of knowledge for providing of efficiency of computer studies is considered.